Development of a MATLAB code for 2D finite element free vibration analysis of structures including the effect of 'pendulum-like' oscillations due to gravity - Goh, Ignatius Qian Zheng (Nanyang Technological University, 2024)
Finite Element Method (FEM) is a powerful numerical tool widely used in mechanical, civil, and aerospace engineering. Typical applications include stress analysis, vibration analysis, buckling analysis, seepage analysis, etc. There are many commercial finite element packages available for finite analysis of the given problem. These are useful for solving common engineering problems. However, it is useful to develop in-house finite element packages for solving research problems in academics.